Empathy in medical students as related to academic performance, clinical competence and gender - Hojat, M; Gonnella, J S; Mangione, S; Nasca, T J; Veloski, J J; Erdmann, J B; Callahan, C A; Magee, M (Medical education, 2002)
Context  Empathy is a major component of a satisfactory doctor–patient relationship and the cultivation of empathy is a learning objective proposed by the Association of American Medical Colleges (AAMC) for all American medical schools. Therefore, it is important to address the measurement of empathy, its development and its correlates in medical schools. Objectives  We designed this study to test two hypotheses: firstly, that medical students with higher empathy scores would obtain higher ratings of clinical competence in core clinical clerkships; and secondly, that women would obtain higher empathy scores than men. Materials and subjects  A 20‐item empathy scale developed by the authors (Jefferson Scale of Physician Empathy) was completed by 371 third‐year medical students (198 men, 173 women). Methods  Associations between empathy scores and ratings of clinical competence in six core clerkships, gender, and performance on objective examinations were studied by using t‐test, analysis of variance, chi‐square and correlation coefficients. Results  Both research hypotheses were confirmed. Empathy scores were associated with ratings of clinical competence and gender, but not with performance in objective examinations such as the Medical College Admission Test (MCAT), and Steps 1 and 2 of the US Medical Licensing Examinations (USMLE). Conclusions  Empathy scores are associated with ratings of clinical competence and gender. The operational measure of empathy used in this study provides opportunities to further examine educational and clinical correlates of empathy, as well as stability and changes in empathy at different stages of undergraduate and graduate medical education.